Islamic Syncretism and Barodak Customs: A Study of Cultural Accommodation Theory in Islamic Anthropology - Rifky Ramdhani; Thobib Al-Asyhar; Yon Machmudi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The barodak tradition practiced by the Tau Samawa community in Sumbawa, West Nusa Tenggara, is a ritual performed before a wedding procession or circumcision, involving the stretching of the bride-to-be’s body using a traditional herb called odak. Although it appears as a physical ceremony, barodak carries deep symbolic and spiritual dimensions, and in local belief, neglecting the ritual may lead to physical or metaphysical disturbances. The problem addressed in this study is the tension perceived between the preservation of local cultural rituals and the internalization of Islamic values within contemporary Samawa society. The purpose of this research is to analyze how the Sumbawa community negotiates the relationship between customary practices and Islamic teachings. Using an ethnographic qualitative method, this study employs direct observation, in-depth interviews, and indigenous documentation to explore culture–religion interaction in the barodak ritual. The findings reveal that the community does not reject Islam; instead, they integrate religious principles into customary practices in a harmonious and adaptive manner. The barodak tradition reflects the community’s capacity to maintain cultural continuity while upholding spiritual norms. The contribution of this research lies in offering a contextual understanding of how local rituals function as a medium for expressing collective cultural and religious identity. It highlights the importance of safeguarding local traditions such as barodak as part of cultural preservation efforts that remain aligned with spiritual and communal values.